2021
DOI: 10.3390/ijms222111797
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Inhibitors: Different Classes, Activities, and Mechanisms of Action

Abstract: Targeting the programmed cell death protein 1/programmed cell death 1 ligand 1 (PD-1/PD-L1) interaction has become an established strategy for cancer immunotherapy. Although hundreds of small-molecule, peptide, and peptidomimetic inhibitors have been proposed in recent years, only a limited number of drug candidates show good PD-1/PD-L1 blocking activity in cell-based assays. In this article, we compare representative molecules from different classes in terms of their PD-1/PD-L1 dissociation capacity measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
(70 reference statements)
0
16
0
Order By: Relevance
“…For the Free-Wilson analysis, the 3-(Phenoxymethyl)biphenyl scaffold was considered as a core scaffold for the selected dataset, and seven R groups substitutions sites were determined on this core. Although many novel and potent BMS-like scaffolds have been recently disclosed by several groups that are actively working in the field [ 58 , 59 ], the scarcity of available datasets prevented us from performing similar analyses for these scaffolds. We are currently working on collecting more data on these scaffolds and the results will be presented in future studies.…”
Section: Methodsmentioning
confidence: 99%
“…For the Free-Wilson analysis, the 3-(Phenoxymethyl)biphenyl scaffold was considered as a core scaffold for the selected dataset, and seven R groups substitutions sites were determined on this core. Although many novel and potent BMS-like scaffolds have been recently disclosed by several groups that are actively working in the field [ 58 , 59 ], the scarcity of available datasets prevented us from performing similar analyses for these scaffolds. We are currently working on collecting more data on these scaffolds and the results will be presented in future studies.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the potency of synthesized inhibitors to disrupt the PD-1/PD-L1 complex, we used homogeneous time resolved fluorescence (HTRF), which is a well-established method for the inhibitory activity of PD-L1 assessment based on RT-FRET effect. ,,, In this binding assay, tagged PD-1 and PD-L1 are labelled with anti-tag reagent that generates FRET signal only when both proteins are bound (in spatial proximity). Presence of inhibitors (small molecules, proteins, and so forth) that disrupt the binding decreases the resulting signal allowing the assessment of the inhibitory activity of tested inhibitors via IC 50 (the half maximal inhibitory concentration).…”
Section: Resultsmentioning
confidence: 99%
“…We have adopted this concept for PD-L1-targeting small molecules and introduced the chelator via a hydrophilic linker unit [128]. In the past years, biological studies have revealed that the binding mode of small molecule inhibitors differs significantly from that of antibodies and peptides (Figure 16) [129]. While both antibodies and peptides bind in a 1:1 molar ratio to PD-L1 and thus prevent the binding of the natural ligand PD-1 in an antagonistic manner, biphenyl- derived low-molecular weight compounds recruit two PD-L1 proteins, leading to the dimerization of the human PD-L1 in vitro.…”
Section: Discussion and Outlookmentioning
confidence: 99%